What works (and doesn't) in reducing recidivism - Latessa, Edward J., author.
1 online resource (xvi, 320 pages)
Keywords: "What Works (and Doesn't) in Reducing Recidivism offers criminologists and students an evidence-based discussion of the latest trends in corrections. Experts Latessa, Listwan, and Koetzle translate the research and findings about what works and doesn't work in reducing recidivism into understandable concepts and terms, presenting them in a way that illustrates the value of research to practice. Over the last several decades, research has clearly shown that rehabilitation efforts can be effective at reducing recidivism among criminal offenders, but it is clear that treatment is not a "one size fits all" approach. Offenders vary by gender, age, crime type, and/or addictions, to name but a few ways, and these individual needs must be addressed by providers. Finally, issues such as leadership, quality of staff, and evaluation efforts affect the quality and delivery of treatment services. While other texts have addressed issues regarding treatment in corrections, this text is unique in that it not only discusses the research on "what works" but also addresses the implementation issues faced as practitioners move from theory to practice, as well as the importance of staff, leadership, and evaluation efforts. This book synthesizes the vast research for the student interested in correctional rehabilitation as well as for the practitioner working with offenders"--